Islamic Education Learning Improvement Through Learning Leadership - Sarwan Sarwan; Imron Rosady (STAIFAS-Press, 2022)
This paper aims to describe the improvement of learning through learning leadership so that the function of principals to improve the quality of inputs through preparing professional educators as a way increasing the quality of Islamic education because if they have professional educators they will do the same. The effective learning process produces outstanding outcomes. The provision of education personnel in decision-making institutions is determined by the education office or school committee. Meanwhile, to improve the professionalism of education personnel, principals bring coaching through supervision activities. Coaching teachers in schools and with other schools to develop the communication, knowledge, and experience of educators by involving teachers in training and workshops. The quality of Islamic education will be achieved with the participation of the community, and for that, the principal also increases promotions to perfect the student recruitment strategy to improve learning, especially in Islamic education learning.